2015
DOI: 10.1177/0363546515599630
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blinded, Placebo-Controlled Clinical Trial Evaluating the Effectiveness of Daily Vibration After Arthroscopic Rotator Cuff Repair

Abstract: High-frequency, low-magnitude vibration did provide acute pain relief on application 6 weeks after arthroscopic rotator cuff repair surgery. However, vibration did not improve tendon-to-bone healing, shoulder range of motion, shoulder strength, or shoulder pain with activities, at rest, and at night when compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…We included 38 studies with 3072 patients for full-text review, as well as in the meta-analysis, as they met the final inclusion criteria. 1 , 4 , 40 , 41 , 42 , 43 , 44 , 46 , 5 , 50 , 52 , 53 , 54 , 56 , 57 , 6 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 20 , 21 , 22 , 23 , 25 , 28 , 29 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 4 , 40 , 41 , 42 , 43 , 44 , 46 , 50 , 52 , 53 , 54 , 56 , 57 The study characteristics of each included cohort are shown in Table I . A forest plot of retear rates is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We included 38 studies with 3072 patients for full-text review, as well as in the meta-analysis, as they met the final inclusion criteria. 1 , 4 , 40 , 41 , 42 , 43 , 44 , 46 , 5 , 50 , 52 , 53 , 54 , 56 , 57 , 6 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 20 , 21 , 22 , 23 , 25 , 28 , 29 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 4 , 40 , 41 , 42 , 43 , 44 , 46 , 50 , 52 , 53 , 54 , 56 , 57 The study characteristics of each included cohort are shown in Table I . A forest plot of retear rates is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in agreement with the small effect we previously reported, 12 but is in stark contrast to the majority of other chronic pain conditions. 40 46 Emerging clinical trial data have further substantiated our observation of limited placebo response in SCI patients. In a recent trial demonstrating the efficacy of botulinum toxin type A (BTXA), fewer than 10% of SCI patients administered saline achieved a meaningful reduction in pain (i.e., >30%).…”
Section: Discussionmentioning
confidence: 95%
“…It is hypothesized that because the PEUU scaffold has a long degeneration time, there are enough time for BMSCs to infiltrate and proliferate without interruption . Moreover, the mechanical stimulation is one of the key factors of tendon-to-bone regeneration in vivo . All these factors would contribute to the successful regeneration of rotator cuff.…”
Section: Discussionmentioning
confidence: 99%